Using Dextran Instead of Egg Yolk in Extender for Cryopreservation of Spermatozoa of Dogs of Different Ages - Yurchuk, T; Pavlovich, O; Petrushko, M (My University, 2022)
Egg yolk is a very common supplement of extenders aimed to protect sperm from cryoinjury, but due to their biological risks and difficulties with media standardization, there is a search for alternative. In addition, sperm cryoresistance can be affected by the initial decrease of their functional characteristics caused by age. The aim of this work was to evaluate the efficiency of using dextran (molecular weight 500 kDa) in the extenders instead of egg yolk for the cryopreservation of spermatozoa of dogs (Chinese Crested breed) of different ages. The obtained ejaculates were divided into three groups depending on the animal’s age: 1–3, 4–6 and 7–10 years old. Sperm was cryopreserved by using 7% glycerol and 20% egg yolk, or 20% dextran. The cryoresistance of spermatozoa of the oldest age category was dramatically decreased, which was manifested in their morphology, motility, and DNA fragmentation rate. There were no differences between the cryoprotectant effect of the dextran-based extender on spermatozoa and the egg yolk-based extender in all age categories of dogs. However, given the benefits of dextran-containing media, its use for the cryopreservation of canine spermatozoa has potential benefits that need to be confirmed by sperm fertilization outcomes.
Yurchuk T, Pavlovich O, Petrushko M. Using Dextran Instead of Egg Yolk in Extender for Cryopreservation of Spermatozoa of Dogs of Different Ages. Animals. 2022; 12(24):3480. https://doi.org/10.3390/ani12243480
Keywords: cryopreservation; sperm; dog; canine; DNA fragmentation